2003
DOI: 10.1074/jbc.m309736200
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Activates CYP7A1 and Bile Acid Biosynthesis

Abstract: Cholesterol 7-␣-hydroxylase (CYP7A1) is the key enzyme that commits cholesterol to the neutral bile acid biosynthesis pathway and is highly regulated. In the current studies, we have uncovered a role for the transcriptional co-activator PGC-1␣ in CYP7A1 gene transcription. PGC-1␣ plays a vital role in adaptive thermogenesis in brown adipose tissue and stimulates genes important to mitochondrial function and oxidative metabolism. It is also involved in the activation of hepatic gluconeogenesic gene expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
3
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 21 publications
7
75
3
1
Order By: Relevance
“…In support of this connection, we found that CYP7A1 was induced by fasting and during streptozotocin induced diabetes (33), two stressful metabolic conditions where insulin signaling and glucose metabolism are compromised. More recently, other reports have also revealed an important role for bile acids in glucose metabolism (34,35).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In support of this connection, we found that CYP7A1 was induced by fasting and during streptozotocin induced diabetes (33), two stressful metabolic conditions where insulin signaling and glucose metabolism are compromised. More recently, other reports have also revealed an important role for bile acids in glucose metabolism (34,35).…”
supporting
confidence: 53%
“…Transient transfection was performed by the calcium phosphate coprecipitation method as described (33). Values represent the mean of duplicates Ϯ S.D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the fatty acid and glycerolipid metabolism pathways may contribute to an improvement of lipid metabolism by repeated treatment with metformin, while some fatty acids might be important in modulating mRNA expression of genes such as G6pc [37]. Interestingly, changes of expression in the bile acid biosynthesis, but not the sterol biosynthesis pathway, were detected; indeed, coordinated transcriptional regulation between bile acids and gluconeogenesis [39,40], as well as suppression of gluconeogenenic genes by bile acid [31], have been reported recently. With regard to amino acid metabolism pathways, such as valine, leucine and isoleucine degradation, lysine degradation, arginine and proline metabolism and tryptophan metabolism, it has previously been reported that protein metabolism is abnormal in type 2 diabetes [41], although its relevance to the action of metformin remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, cholesterol is synthesized and degraded in the liver accordingly to the needs by other tissues (12). Cyp7A1 is the key rate-limiting enzyme controlling cholesterol degradation through hepatic synthesis of bile acids (13,14). Efflux and influx through scavenge receptor B1 (SR-B1), low-density lipoprotein (LDL) receptor, and ABC transporters also plays an important role in regulating cholesterol levels (15)(16)(17).…”
mentioning
confidence: 99%